A training model for revitalization procedures. (10th April 2017) - Widbiller, M.; Ducke, S.; Eidt, A.; Buchalla, W.; Galler, K. M.
Abstract: Aim: To develop an inexpensive simulation model for training of revitalization procedures. Methodology: A replica of an immature maxillary central incisor was equipped with a mock blood reservoir at the root apex and embedded in a plaster model. Mock blood consisted of water supplemented with red pigments and fibrinogen, whilst thrombin was inserted into the root canal to allow for clot formation. Results: A true‐to‐life training model for revitalization procedures was established, where the induction of bleeding and formation of a blood clot can be mimicked. The model can be fastened to a patient mannequin and thus closely simulate the clinical setting. Conclusions: The newly developed model can be used for training purposes, both for dental students and for practitioners, to perform the treatment steps of a revitalization procedure.